Effect of Electroacupuncture Preconditioning on Inflammatory Factors of Rabbits after Spinal Cord Ischemia-Reperfusion Injury - Mengli YAO; Xianghua CHEN; Zhaohui CHEN; Hai WANG (康复学报)
Objective:To observe the effects of electroacupuncture preconditioning on the pathological changes of spinal cord tissue and the expression of inflammatory cytokines such as interleukin-1β(IL-1β), interleukin-6(IL-6), tumor necrosis factor-α(TNF-α), interleukin-1 receptor antagonist(IL-1Rα)after spinal cord ischemia-reperfusion injury, and to explore the protective mechanism of electroacupuncture on spinal cord ischemia-reperfusion injury in rabbits.Methods:A total of twenty-four New Zealand white rabbits were randomly divided into the sham operation group, the model group and the electroacupuncture group according to the random number table method, with eight cases in each group.The model was made by Zivin method in the model group and the electroacupuncture group, the abdominal cavity was opened after intravenous anesthesia at ear margin, the abdominal aorta was exposed and temporarily clamped, and the rabbit model of spinal cord ischemia-reperfusion injury was established after ischemia for thirty minutes.The model preparation and experimental animal treatment of the sham operation group were the same as those of the model group, however, the dissection was fully exposed without clamping the abdominal aorta.At thirty minutes before the induction of rabbit spinal cord ischemia-reperfusion model, SDZ-II electroacupuncture instrument was used to acupuncture bilateral"Xuanzhong"and"Yanglingquan"acupoints in the electroacupuncture group, intervention for thirty minutes.All rabbits were killed after intervention for twelve hours, and the L2-5 segments of spinal cord tissue were captured.HE staining method was used to observe the pathological changes of spinal cord tissues in the three groups; Immunohistochemical method was used to observe the localization and content changes of IL-1β, IL-6 and TNF-α; Enzyme-linked immunosorbent assay(ELISA)was used to detect the contents of IL-1β, IL-6, TNF-α and IL-1Rα in serum before modeling and 4, 8, 12 hours after ischemia-reperfusion.Results:①HE staining results: compared with the sham operation group, the number of neurons in spinal cord tissue in the model group decreased, the color of nucleus and cytoplasm of cells became lighter, and the boundary of nuclear membrane was not clear.In severe cases, the nucleus dissolved or even nucleolus disappeared, there were transparent areas around cells, and axons showed different degrees of degeneration such as enlargement, swelling and disappearance; compared with the model group, the number of neurons in the electroacupuncture group increased, the structure of most neurons was clear, the atrophy degree of nucleolus and nucleus was light, only a small amount of cells became deformed and necrosis, the damage degree of cells were lighter, and the density of surviving neurons increased.②Immunohistochemistry results: compared with the sham operation group, the expressions of IL-1β, IL-6 and TNF-α of spinal cord tissue in the model group were significantly increased(P<0.05);compared with the model group, the contents of IL-1β, IL-6 and TNF-α in the spinal cord of rabbits in the electroacupuncture group were significantly decreased(P<0.05).③ELISA results: Before modeling, there was no significant difference in the three groups(P>0.05);compared with before modeling, the expressions of IL-1β, IL-6, TNF-α, IL-1Rα in serum of the three groups increased in different degrees at 4, 8 and 12 h after ischemia-reperfusion, with significantly significance(P<0.05);compared with the sham operation group at the same time, the expressions of IL-1β, IL-6, TNF-α and IL-1Rα in the model group increased significantly at 4, 8 and 12 h after reperfusion(P<0.05);compared with the model group at the same time, the expression of IL-1β and TNF-α in the electroacupuncture group decreased significantly at 4, 8, 12 h after reperfusion(P<0.05).Conclusion:Electroacupuncture pretreatment can effectively alleviate the pathological injury of spinal cord and has a good protective effect on spinal cord ischemia-reperfusion injury, which may be related to inhibit the expression of IL-1β, IL-6 and TNF-α and promote the expression of IL-1Rα.